Endoscopic appearance of esophageal xanthoma - Hamada, Kenta; Uedo, Noriya; Kubo, Chiaki; Tomita, Yasuhiko; Ishihara, Ryu; Yamasaki, Yasushi; Omori, Masayasu; Arao, Masamichi; Suzuki, Sho; Iwatsubo, Taro; Kato, Minoru; Tonai, Yusuke; Shichijo, Satoki; Matsuura, Noriko; Nakahira, Hiroko; Kanesaka, Takashi; Yamamoto, Sachiko; Akasaka, Tomofumi; Hanaoka, Noboru; Takeuchi, Yoji; Higashino, Koji; Okada, Hiroyuki; Iishi, Hiroyasu (Endoscopy International Open, 2019)
Background and study aims Esophageal xanthomas are considered to be rare, and their endoscopic diagnosis has not been fully elucidated. The aim of the present study was to determine the characteristics of the endoscopic appearance of esophageal xanthomas.Patients and methods This was a retrospective study of consecutive patients with histologically diagnosed esophageal xanthomas at a referral cancer center in Japan. The endoscopic appearance, by magnifying or image-enhanced endoscopy, and histological findings of esophageal xanthomas were investigated.Results Seven patients (six men and one woman) were enrolled. All of the patients had a solitary lesion, and the median size was 2 mm (range, 1 – 5 mm). Conventional white-light endoscopy showed the lesions as flat areas with yellowish spots in four cases and slightly elevated yellowish lesions in three cases. Magnifying endoscopy, performed in six patients, revealed the lesions as areas with aggregated minute yellowish spots with tortuous microvessels inside. Magnifying narrow-band imaging contrasted the yellowish spots and microvessels better than white-light endoscopy. In all lesions, histological examination showed that the yellowish spots corresponded to papillae filled with foam cells. The foam cells were strongly immunopositive for CD68, and in all lesions, CD34-positive intrapapillary capillaries surrounded the aggregated foam cells. The different morphologies of the flat and slightly elevated lesions corresponded to different densities of papillae filled with foam cells.Conclusions Magnifying endoscopy revealed minute yellowish spots with tortuous microvessels inside. These correspond well with histological findings and so may be useful in the diagnosis of esophageal xanthomas.